THEME AND THEMATIC PROGRESSION ANALYSIS OF UNDERGRADUATE STUDENT'S THESIS - Aziza, Fatayatul (2016)
The present study focuses on investigating the choice of Themeand Thematic progression in one of the best theses in Jabal Ghafur University. This study particularly attempts to find the contribution of Theme and Thematic progression to the textual cohesion of a thesis from a best thesis of Jabal Ghafur University. In addition, the present study attempts to obtain a portrait of linguistic features of a thesis which achieves the degree of cohesion. To achieve its objectives, this study employs a descriptive-qualitative research design embracing the characteristics of a case study approach. The data obtained from the best student's thesis were analyzed through the theory of Theme system and Thematic progression developed by Eggins (1994, 2004). Regarding theme and thematic progression choice, the results of the study show that three types of Theme Topical Theme, Interpersonal Theme, and Textual Themeare realized in the student's thesis. Additionally, Theme Reiteration, Zig-Zag pattern,and Multiple Theme pattern are types of thematic progression patterns found in the student's thesis. Concerning the contribution of Theme and its progression to the textual cohesion of the text, the result of the study reveals that the student built the textual cohesion of her text through the use of cohesive relationship (textual Theme) aimed to relate each idea in the text, the use of semantic ties (marked topical Theme)aimed to build contextual frame in the text, the use of theme reiteration aimed to provide strong and clear focus of the text, the use of zig-zag pattern aimed to give sense of cumulative development of the text, and the use of multiple theme pattern aimed to support the coherency of text in global level.It is recommended that future related research should analyze and compare the use of theme and thematic progression in students' theses across disciplines and languages. ;-- Penelitian ini bertujuan untuk mengetahui penggunaan "Theme dan Thematic progression" di salah satu skripsi terbaikUniversitas Jabal Ghafur. Penelitian ini khususnya bertujuan untuk melihat kontribusi "Theme dan Thematic progression" untuk kohesi tekstual tesis terbaik di Jabal Ghafur University. Selain itu, penelitian ini mencoba untuk memperoleh potret fitur linguistik dari tesis yang baik dan 'cohesive'.Untuk memperoleh jawaban dari pertanyaan penelitian, penelitian ini menggunakan metode deskriptif-kualitatif yang bercirikan studi kasus. Data yang diperoleh dari tesis mahasiswa terbaik ini dianalisis menggunakan teori "Theme dan thematic progression" yang dikembangkan oleh Eggins (1994, 2004). Berkaitan dengan penggunaan "Theme dan Thematic progression" di teks siswa, hasil penelitian menunjukkan bahwa tiga jenis Tema yang digunakan siswa dalam teks nya "Topical Theme, Interpersonal Theme, and Textual Theme". Selain itu, pola "thematic progression" yang digunakan siswa dalam teks nya adalah "Theme Reiteration, Zig-Zag pattern,and Multiple Theme pattern". Mengenai kontribusi"Theme dan Thematic progression"terhadap tingkat kohesi tekstual teks, hasil penelitian menunjukkan bahwa siswa membangun kohesi tekstual teks nya melalui penggunaan Textual Theme yang bertujuan untuk menghubungkan setiap gagasan dalam teks, penggunaan semantic ties (marked topical Theme) bertujuan untuk membangun kerangka kontekstual dalam teks, penggunaan pola theme reiteration bertujuan untuk memberikan fokus yang kuat dan jelas dari teks, penggunaan pola zig-zagbertujuan untuk mengembangkan teks, dan penggunaan pola multiple theme bertujuan untuk mendukung koherensi teks di tingkat global. Disarankan bahwa penelitian selanjutnya yang terkait seharusnya menganalisis dan membandingkan penggunaan"Theme dan thematic progression" di tesis berbagai disiplin ilmu dan bahasa.